Developing Collaborative Skills for High School Students in Lao People’s Democratic Republic in Solving Mathematical Problems - Phommanichan, Vongsy; Cuong, Tran Viet (International Journal of Membrane Science and Technology, 2023)
The research article aims to develop collaborative problem-solving skills in high school mathematics education within the Lao People’s Democratic Republic. It introduces five methods that enhance collaboration in solving mathematical problems, offering comprehensive descriptions and implementation strategies. The research equips teachers with effective strategies and creates opportunities for students to engage in collaborative problem-solving. However, the study is limited by its narrow focus on the specific context of the Lao People’s Democratic Republic. Future research should explore the adaptability of these methods in diverse cultural and educational settings. To further advance collaborative problem-solving in mathematics education, future research should investigate the effectiveness of these methods across various grade levels and cultural contexts.